Evaluation of risk scores for risk stratification of acute coronary syndromes in the Myocardial Infarction National Audit Project (MINAP) database. - Clive Weston (Heart, 2008)
The objective was to compare the performance of a number of risk models in predicting outcome for patients presenting to hospital with acute coronary syndrome (ACS) using data obtained in the Myocardial Infarction National Audit Project (MINAP) - a national registry of care provided by hospitals in England and Wales. There were 100 686 cases of ACS between 2003 and 2005.The performance was expressed as the C-index for predicting the likelihood of death over the time period for which each model was designed. The C-indexes were: PURSUIT C-index 0.79 (95% confidence interval 0.78 to 0.80); GUSTO-1 0.80 (0.79 to 0.81); GRACE in-hospital 0.80 (0.80 to 0.81); GRACE 6-month 0.80 (0.79 to 0.80); SRI 0.79 (0.78 to 0.80); and EMMACE 0.78 (0.77 to 0.78). EMMACE maintained its ability to discriminate 30-day mortality throughout different ACS diagnoses. For all models the discriminative performance was reduced in patients with diabetes, chronic renal failure or angina. Simpler risk models had comparable performance to more complex risk models.